AB0388 IMPROVEMENT OF PATIENT-REPORTED OUTCOMES IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME UNDERGOING CPAP-TREATMENT. (2nd June 2020) - Seng, M.; Frye, B. C.; Vollmer, L.; Kollert, F.; Voll, R.; Finzel, S.
Abstract : Background: Fatigue is a frequent symptom in primary Sjögren's Syndrome (pSS) determining health-related quality of life in many patients. Earlier studies could show that sleep apnea syndrome (SAS) is associated with patient-reported outcomes in pSS-patients [1]. Objectives: To investigate whether treatment of an underlying SAS improves disease activity in pSS-patients. Methods: 14 female pSS-patients from our rheumatology outpatient clinic were enrolled and screened for SAS; continuous positive airway pressure (CPAP)-treatment was initiated in patients with a sleep apnea/hypopnea index >5/h and a respiratory disturbance index >15/h sleeping time (pSS treated with CPAP: pSS+; pSS untreated: pSS-). As controls, 11 SAS-patients (4 female) scheduled for initiation of CPAP-treatment were recruited from pulmonology department. In pSS, ESSDAI, ESSPRI, pain and patient global health on a visual analogue scale from 0-100mm were recorded. In both groups CRP, ESR, depression (PHQ-9), fatigue (FACIT), daytime sleepiness (EPS), and salivary gland ultrasound (SGUS) of the parotid and submandibular glands (PG; SMG) were obtained [2]. Data were collected at baseline (BL) and month 3 (M3). A p-value <0.05 was deemed significant. Results: 6 pSS-patients were diagnosed with SAS and underwent CPAP-initiation, as well as all SAS-patients. Table 1 shows means ± SD of all assessments. EPS indicated normal sleep propensity in all groups at both time points. Fatigue was severe in all groups at BL. Numerically in SAS and pSS+, fatigue and depression trended towards improvement between BL and M3. Depression scores were moderate in all groups at BL; in SAS, PHQ-9 score showed a trend towards improvement at M3. SGUS grades 0 or 1 (i.e. normal or unspecific SGUS pattern) were found in 46.43% of PG and SMG at BL, in 40.39% at M3 in pSS, and in 100% in SAS at both time points. Grades 2 or 3 (pSS-typical US-pattern or gland destruction) were exclusively found in pSS at BL (53.57%) and M3 (59.62%). pSS-SGUS scores worsened irrespective of CPAP-treatment. Conclusion: Even though this is only preliminary data of a small fraction of patients who completed M3 so far, there is already a clear tendency towards reduced fatigue, inflammatory markers and depression both in the CPAP-treated pSS and in the SAS-patients compared to the non-CPAP-treated pSS-patients. References: [1]Usmani ZM Sleep Medicine 2012; 2. Jousse-Joulin S Ann Rheum Dis. 2019 Disclosure of Interests: Magdalena Seng: None declared, Björn Christian Frye: None declared, Lydia Vollmer: None declared, Florian Kollert Employee of: Novartis, Reinhard Voll: None declared, Stephanie Finzel: None declared